Adjunctive rifampin therapy for diabetic foot osteomyelitis: A protocol for systematic review and meta-analysis. Issue 22 (29th May 2020) - Zhang, Yanli; Wang, Shengju; Liu, Min; Yao, Shasha; Fang, Song; Cheng, Haiping; Chen, Qiu
Abstract: Introduction: The prevalence of diabetes continues to rise around the world. Diabetic foot is a serious complication of diabetes, and diabetic patients with diabetic foot osteomyelitis (DFO) have a fourfold increased risk of amputation, usually indicating death. Therefore, it is particularly important to seek a more effective treatment for DFO. The treatment of DFO varies from person to person, and antimicrobial therapies vary widely. A large number of clinical studies have shown that rifampicin adjuvant therapy can reduce the rate of amputation and mortality in DFO patients. However, there is no systematic summary of clinical evidence, which limits the clinical application of rifampicin. Therefore, we attempted to provide high-quality evidence for the clinical efficacy and safety of rifampin in the adjuvant treatment of DFO through this meta-analysis. Methods: English literature is mainly searched in Cochrane Library, PubMed, EMBASE and Web of Science, while Chinese literature is from CNKI, CBM, VIP and Wangfang databases. At the same time, we will search clinical registration tests and gray literature. Two methodologically trained researchers will read the title, abstract, and full text, and independently select qualified literature based on inclusion and exclusion criteria. Binary data is expressed as relative risk, continuous data is expressed as mean difference or standard mean difference. The final data are synthesized using a fixed effect model or a random effect model, depending on the presence of heterogeneity. In the end, the patient's amputation rate and mortality were the main research indicators. Survival rate, HbA1c, serum creatinine, changes in ulcer area, and SF-36 quality of life assessment were used as secondary indicators. We will perform a sensitivity analysis to assess the stability of the results. Then the publication bias was evaluated by funnel plot analysis and Egger test. Finally, we will use a "recommendation grading, evaluation, formulation and evaluation" system to assess the quality of the evidence. All data analysis will be meta-analyzed by the statistical software RevMan software version 5.3. Results: This study will provide a high-quality comprehensive report on the effectiveness and safety of rifampicin in the treatment of DFO, and our findings will be published in peer-reviewed journals. Conclusion: This systematic review and meta-analysis will provide a comprehensive summary and careful evaluation of rifampicin as an adjuvant treatment of DFO with a view to providing multiple options for clinical treatment of the disease. Registration number: is INPLASY202040084.